Cortical spreading depolarization in lesional epilepsy surgery - San Juan Orta, Daniel; Márquez, Katia; Díaz-Peregrino, Roberto; Alonso-Vanegas, Mario; Santos, Edgar (Clinical neurophysiology, 2018)
Introduction - Cortical spreading depressions (CSDs) are waves of near-complete cellular depolarization that spread slowly across the cortical surface (2-5mm/min) and result in transient loss of cell signaling capabilities. CSDs is a biomarker of neuronal damage described in several clinical hypoxic-ischemic conditions However, only has been found in one patient operated for Giant pituitary adenoma. - Methods - This is a prospective study that included adult patients undergoing elective craniotomy for epileptogenic supratentorial lesions lasting >2h. Electrocorticographic recordings were obtained from time of dural opening through the time of dural closure, using a standard 1×8 silver electrode coupled with a full-spectrum DC amplifier (0-45Hz, Notch: 60Hz). We analyzed the clinical and socio-demographic characteristics. The data were processed using the COSBID research group methodology to evaluate for slow potential changes coupled with suppression of high-frequency ECoG propagating across the electrodes. Describe statistics were used. - Results - We included 16 patients, mean age 37 (19-75) years-old, 50% male, underwent 4 callosotomies and 12 temporal lesionectomies (3 cortical dysplasia, 2 cavernomas, 5 gliomas and 2 dermoid cystic). All the patients had history of symptomatic epilepsy and none had postsurgical complications and only 2 patients post-callosotomy continued with seizures at 6months of follow-up. We didn’t find any CSD during these neurosurgeries. - Conclusion - CSDs were absent during lesional epilepsy surgery. Future studies are needed to confirm these findings.